2020
DOI: 10.1016/j.ijbiomac.2020.07.117
|View full text |Cite
|
Sign up to set email alerts
|

Design of a multi-epitope vaccine against SARS-CoV-2 using immunoinformatics approach

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused COVID-19 disease in China. So far, no vaccine has licensed to protect against infection with COVID-19, therefore an effective COVID-19 vaccine needed. The aim of this study was to predict antigenic peptides of SARS-CoV-2 for designing the COVID-19 vaccine using immunoinformatic analysis. In this study, T and B-cell epitopes of S protein were predicted and screened based on the antigenicity, toxicity, allergenicity, and cross-reactivity with hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…In recent months, several authors already reported the MEBP vaccine candidates against SARS-CoV-2 using reverse vaccinology approach. Studies published by Naz et al ( 2020 ) and Sanami et al ( 2020 ) predicted both B- and T-cell epitopes of S protein alone for designing a MEBP vaccine candidate against SARS-CoV-2. Sarkar et al ( 2020 ) reported N and S proteins as target antigens for prediction of B- and T-cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent months, several authors already reported the MEBP vaccine candidates against SARS-CoV-2 using reverse vaccinology approach. Studies published by Naz et al ( 2020 ) and Sanami et al ( 2020 ) predicted both B- and T-cell epitopes of S protein alone for designing a MEBP vaccine candidate against SARS-CoV-2. Sarkar et al ( 2020 ) reported N and S proteins as target antigens for prediction of B- and T-cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…This is because almost all prediction methods (discussed in Section 2.2.1) require specifying the HLA allele for predicting associated epitopes. However, a close inspection of the related studies revealed that this was due to either non-reporting of HLA allele restriction of the predicted epitopes (e.g., Sarkar et al [ 161 ]), or cases where only the number of unique HLA alleles associated with the predicted epitopes were reported without specifying the individual correspondences (e.g., Sanami et al [ 163 ]). As for the studies leveraging the immunological data of SARS-CoV from public databases, the SARS-CoV epitopes having no HLA class information were assigned the “NA” HLA class.…”
Section: Comparison Of Studies Predicting Sars-cov-2 Epitopesmentioning
confidence: 99%
“…VaxiJen v2.0 server was used in examining the antigenicity potential of the protein using non-alignment dependent algorithm but focuses on the physiochemical attributes of the selected prototype vaccine (Yasmin et al 2016 ; Sanami et al 2020 ). ANTIGENPro is a free server which functions with specific microarray data for the evaluation of protein antigenicity index.…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of the server was reported to be 76% based on cross-validation experiments (Magnan et al 2010 ; Kalita et al 2019 ). AllerTOP v2.0 server (employs machine learning techniques like amino acid E-descriptors, auto and cross variance transformation and the k nearest neighbours, for the allergenic classification with accuracy of 85.3% (Sanami et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%